Analisis Dinamika Rasio Vibrio terhadap Total Bakteri sebagai Indikator Risiko Penyakit pada Budidaya Udang di Desa Jalange, Kecamatan Mallusetasi - Bagus Ansani Takwin; Gabriella Augustine Suleman; Adimas Bagus Fahturohman; Achamd Husein Nyompa; Yakub Suleman (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2026)
Intensive farming of Pacific white shrimp (Litopenaeus vannamei) is highly susceptible to microbiological imbalance due to the accumulation of organic matter, which can increase the risk of bacterial diseases, particularly those associated with the Vibrio group. This study aimed to analyze the dynamics of the Vibrio-to-total bacteria ratio throughout the culture cycle of Pacific white shrimp in South Sulawesi and to evaluate its potential as an indicator of disease risk. The research was conducted in a super-intensive Pacific white shrimp pond in Barru Regency over a single production cycle. Pond water samples were collected twice weekly and analyzed using the Total Plate Count (TPC) method to determine total bacterial abundance and the Total Vibrio Count (TVC) method on Thiosulfate Citrate Bile Salts Sucrose (TCBS) agar to quantify Vibrio populations. The observed parameters included total bacterial count, yellow Vibrio colonies, green Vibrio colonies, and the Vibrio-to-total bacteria ratio. The results showed that total bacterial abundance fluctuated within the range of 10⁶–10⁷ colony-forming units per milliliter (CFU mL⁻¹) throughout most of the culture period. Yellow Vibrio colonies consistently exhibited higher abundance than green Vibrio colonies during almost all observation periods. The Vibrio-to-total bacteria ratio displayed dynamic temporal fluctuations with several pronounced peaks, particularly during the final stage of cultivation, indicating an increasing relative dominance of Vibrio within the microbial community. These findings suggest that the Vibrio-to-total bacteria ratio provides a more comprehensive assessment of microbial community balance than absolute Vibrio abundance alone. Therefore, this parameter has strong potential to serve as an early indicator of disease risk in intensive Pacific white shrimp farming systems.